Factors influencing undergraduate students' desire to become chartered accountants: evidence from an emerging economy, Bangladesh - Ahmed, Ibrahim (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.